Determinants of Varietal Replacement of Haricot Bean by Farmers in Boricha District, Southern Ethiopia - Ganewo, Zerhun; Tefera, Tewodros; Hirpa, Adane (Journal of Science and Development, 2017)
Seed is a fundamental input in crop production, which plays a significant role in enhancing productivity. Associatedwith seed, the choice and the decision to replace crop varieties in use are critical to increase productivity. This studyexamined determinants of varietal replacement among farmers producing Haricot bean varieties in Boricha district.Four kebele administrations and 162 sample respondents were selected using a multi-stage sampling procedure anddata were collected by using a structured questionnaire. The findings show that improved haricot bean varietiespromoted by the extension system were released during the last 6 to 12 years. Farmers mainly grow old varieties andhence varietal replacement is low. From total sample respondents, 77% had grown varieties that were released fromresearch centers in the past 6 to 12 years whereas the remaining 23% had grown Red Wolaita, which was releasedfour and half decades ago and now considered as a local variety. Out of 162 farmers, 72% of sampled farmersreplaced the old variety by Hawassa Dume, which was released in 2008 and is the most recent variety available in thedistrict. The Logistic regression model showed that age of household head, size of landholding, market price ofvarieties used for replacement, livestock ownership measured in Tropical Livestock Unit (TLU), availability ofrecently released varieties, participation on extension demonstration, and perception about yield of varieties used forreplacement significantly affected varietal replacement decisions. Hence, it is important to enhance resourceendowment of households, improve access for recently released varieties, integrate growers with high value marketand organize extension demonstration of improved varieties to facilitate varietal replacement.